2016
DOI: 10.5812/ijhrba.31450
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Restructuring Based on Metaphor Therapy to Challenge the Irrational Beliefs of Drug Addicts Undergoing Buprenorphine Treatment

Abstract: Background: The use of metaphors rather than direct suggestions of treatment can help to weaken defense mechanisms against any functional changes and so cause an increase in the effectiveness of therapeutic interventions. Objectives: This research was conducted with the aim of determining the effectiveness of individual metaphor therapy (IMT) in reducing the irrational beliefs and cognitive restructuring of drug addicts undergoing buprenorphine treatment. Patients and Methods: Using a randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…intentional use of metaphor as more helpful than other sessions (Martin, Cummings, & Hallberg, 1992). Additionally, empirical evidence has demonstrated that metaphor is effective in ameliorating irrational beliefs (Komasi, Saeidi, Zakiei, Amiri, & Soltani, 2016), as well as in changing catastrophizing and pain biology knowledge (Gallagher, Mcauley, & Moseley, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…intentional use of metaphor as more helpful than other sessions (Martin, Cummings, & Hallberg, 1992). Additionally, empirical evidence has demonstrated that metaphor is effective in ameliorating irrational beliefs (Komasi, Saeidi, Zakiei, Amiri, & Soltani, 2016), as well as in changing catastrophizing and pain biology knowledge (Gallagher, Mcauley, & Moseley, 2013).…”
mentioning
confidence: 99%
“…We further sought to identify the specific brain regions activated by therapeutic metaphor, because empirical evidence has demonstrated that therapeutic metaphor is more effective in alleviating mental distress (Gallagher et al, 2013;Komasi et al, 2016), and the insightfulness experiences produced by therapeutic metaphor in the micro-counseling scenarios could predict the reduction of negative affect after the intervention (Hu et al, 2018). The neuroimaging studies demonstrated that metaphor comprehension induced different activities than did literal sentences; metaphor significantly increased signal changes in the left inferior frontal gyrus (IFG; Brodmann area (BA) 45/47), as well as in the left inferior and middle temporal gyri (ITG and MTG, respectively) (Rapp et al, 2004;Bohrn et al, 2012;Rapp et al, 2012).…”
mentioning
confidence: 99%
“…The center's treatment protocol is multi-component. Except for medication delivery, the protocol simultaneously involves psychological interventions and social worker services (2,3). According to available reports, these centers have been able to control drug abuse.…”
Section: Dear Editormentioning
confidence: 99%
“…Drug addiction, defined as a chronic, progressive, and destructive illness, is common throughout the world (1). although there is plenty of studies on heart risk factors among smokers (2), there is a shortage of studies on cardiovascular diseases (CVDs) risk factors among drug addicts (3).…”
Section: Introductionmentioning
confidence: 99%